Functional Roles of Dopamine D(2) and D(3)Autoreceptors on Nigrostriatal Neurons Analyzed by Antisense KnockdownIn Vivo - Tepper, James M. (J Neurosci, 1997)
Two different 19-mer antisense oligodeoxynucleotides complementary to the initial coding regions of dopamine D(2) or D(3) receptor mRNA were infused unilaterally into the substantia nigra of rats for 3–6 d to suppress synthesis of D(2) and/or D(3) receptors on substantia nigra dopaminergic neurons, thereby producing specific reductions of D(2) and/or D(3) receptors. Autoradiographic receptor binding revealed that D(2) and D(3)antisense oligodeoxynucleotides specifically and significantly reduced D(2) or D(3) binding in the ipsilateral substantia nigra, respectively, without affecting dopamine receptor binding in the neostriatum. Either D(2) or D(3) antisense oligodeoxynucleotides greatly attenuated the ability of apomorphine to inhibit dopaminergic neurons in vivo, an effect that was potentiated by simultaneous administration of D(2) and D(3) antisenses. Despite these effects, neither the rate nor the pattern of spontaneous activity of antisense-treated nigrostriatal neurons differed from those in the control groups. The proportion of antidromic responses consisting of full spikes from antisense-treated rats was significantly greater, and the mean antidromic threshold was significantly lower than in controls, indicating that autoreceptor knockdown increased both somatodendritic and terminal excitability. These data demonstrate that selective reduction of specific dopamine receptor subtypes by antisense infusion can be effected in vivo, and that nigrostriatal neurons express both D(2) and D(3) autoreceptors at their somatodendritic and axon terminal regions. Although the somatodendritic and terminal autoreceptors modulate dendritic and terminal excitability, respectively, the interaction of endogenously released dopamine with somatodendritic autoreceptors does not appear to exert a significant effect on spontaneous activity in anesthetized rats.